Measurements of top-quark pair differential and double-differential cross-sections in the l+ jets channel with pp collisions at s=13 TeV using the ATLAS detector - Aad, Georges; Andrei, George Victor; Antel, Claire; Dunford, Monica; Franchino, Silvia; Geisler, Manuel Patrice; Jongmanns, Jan; Klassen, Martin; Kugel, Andreas; Meyer zu Theenhausen, Hanno; Napolitano, Fabrizio; Ott, Philipp; et al. (The European physical journal. C, Particles and fields, 2019)
Single- and double-differential cross-section measurements are presented for the production of top-quark pairs, in the lepton + jets channel at particle and parton level. Two topologies, resolved and boosted, are considered and the results are presented as a function of several kinematic variables characterising the top and $$t\bar{t}$$tt¯ system and jet multiplicities. The study was performed using data from pp collisions at centre-of-mass energy of 13 TeV collected in 2015 and 2016 by the ATLAS detector at the CERN Large Hadron Collider (LHC), corresponding to an integrated luminosity of $$36~fb^{-1}$$36fb-1. Due to the large $$t\bar{t}$$tt¯ cross-section at the LHC, such measurements allow a detailed study of the properties of top-quark production and decay, enabling precision tests of several Monte Carlo generators and fixed-order Standard Model predictions. Overall, there is good agreement between the theoretical predictions and the data.